Detection of bladder tumors with 3-dimensional sonography and virtual sonographic cystoscopy - Kocakoc, Ercan; Kiris, Adem; Orhan, Irfan; Poyraz, A. Kursad; Artas, Hakan; Firdolas, Fatih (Amer Inst Ultrasound Medicine, 2008)
Objective. Bladder tumors are among the most common types of malignant neoplasms of the urinary tract. The purpose of this study was to evaluate the potential value of 3-dimensional (3D) sonography and sonographic cystoscopy in detection of bladder tumors. Methods. Thirty-one patients with suspected or known bladder tumors were included this study. All patients underwent 3D sonography and conventional cystoscopy within 15 days. The number, size, location, and morphologic features of the lesions were evaluated on gray scale, 3D virtual, and multiplanar reconstruction images obtained from the patients. The results of 3D sonographic cystoscopy were compared with the findings from conventional cystoscopy, which was considered the reference standard. Results. Twenty-eight (90.3%) of 31 3D virtual sonographic cystoscopic studies had good or excellent image quality. Conventional cystoscopy revealed 47 lesions in 22 of 28 patients; 3D sonographic virtual cystoscopy showed 41 (87.2%) of 47 lesions. Three-dimensional virtual sonography alone had sensitivity of 96.2%, specificity of 70.6%, a positive predictive value of 93.9%, and a negative predictive value of 80% for tumor detection. The combination of gray scale sonography, multiplanar reconstruction, and 3D virtual sonography had sensitivity of 96.4%, specificity of 88.8%, a positive predictive value of 97.6%, and a negative predictive value of 84.2% for tumor detection. Conclusions. Three-dimensional sonography is a promising alternative noninvasive technique for use in detection of bladder tumors, their localization, and perivesical spreading. The location, size, and morphologic features of the tumors shown on 3D sonography agreed well with the findings of conventional cystoscopy.
Keywords: bladder; neoplasm; sonography; 3-dimensional virtual cystoscopy